The Evolution of Relationship Marketing (RM) Towards Customer Relationship Management (CRM): A Step towards Company Sustainability - Wahab, Samsudin (Information Management and Business Review, 2010)
This paper provides an overview of relationship marketing (RM) and how it evolves to customer relationship management (CRM). Since marketing continuum is the basic concept for relationship marketing it is apt that marketing continuum is explained first. The reviewed literature than discussed the evolution of marketing from the four P’s principle towards more challenge structure combining environment factors and global market scenario ending with customer relationship management philosophy. This paper developed from the rational theories that are very relevant for the practitioners’ who are alert to the environmental changes. This paper ends with more applicable of customer relationship management concepts that are most recent tools to be considered for company growth and sustainability in the millennium age.